SOSIALISASI PENGELOLAAN LIMBAH PETERNAKAN DAN PERTANIAN UNTUK MENINGKATKAN KESEHATAN MASYARAKAT DI DESA BATU KUMBUNG KECAMATAN LINGSAR - Ni Wayan Sri Suliartini; Irmayani Irmayani; Ira Maisopa; Jumratul Ismayanti; Khairina Khairina; Julizar Aulida AP; Devi Aulia Ramadhan; Kesan Oktavian Ali; Muh. Andi Wirya Sintanu; Zen Alvin; Amirul Mukmin (Universitas Mataram, 2023)
Batu Kumbung Village is one of the villages in West Lombok Regency which is known for its extensive agricultural land, fertile soil, abundant water sources, and favorable climate. So far, the use of inputs for food cultivation and horticulture still uses inorganic fertilizers, even though many cattle breeders produce manure in the village and most of the agricultural land produces agricultural waste which is not utilized. This PKM activity aims to increase public knowledge regarding the management of livestock and agricultural waste for public health. This activity was held on Friday, August 4 2023 at the house of a member of the Jasmine Farming Women's Group. The method used in socialization is Andragogy, namely the learning process in counseling based on the principles of adult learning which is carried out by presenting counseling material, followed by questions and answers (discussion). Participants who attended and took part in this activity were 25 members of the Women's Farmers Group, and during the activity the participants were enthusiastic in taking part in this activity. The results of this activity showed an increase in participants' knowledge regarding the management of livestock and agricultural waste such as compost and liquid organic fertilizer. On the other hand, spontaneity can also increase public awareness of the dangers of livestock waste to health. This was proven by the enthusiasm of the participants in participating in the activity from start to finish without anyone leaving the place where the activity took place. Apart from that, many participants responded by asking questions and providing suggestions and hoped that this activity could be carried out sustainably. Based on this, it can be concluded that there has been an increase in community knowledge in Batu Kumbung Village regarding the management of livestock and agricultural waste.